Adherence to mediterranean diet in patients with inflammatory bowel disease. (December 2021) - Fiorindi, Camilla; Dinu, Monica; Gavazzi, Elena; Scaringi, Stefano; Ficari, Ferdinando; Nannoni, Anita; Sofi, Francesco; Giudici, Francesco
Summary: Background & aims: Mediterranean diet may be beneficial for inflammatory bowel disease (IBD). The aim of this study was to evaluate the level of adherence to MD in Italian patients with IBD. Methods: Eighty consecutive outpatients with IBD, 62 with Crohn's Disease (CD) and 18 with Ulcerative Colitis (UC) were included in the study. Demographic and clinical data, previous and current medical history, nutritional status and Quality of Life (QoL) assessed with the Short Inflammatory Bowel Disease Questionnaire (SIBDQ) were assessed. Adherence to MD was studied with the Medi-Lite questionnaire. Results: IBD patients reported a mean Medi-Lite score of 10.4 with no significant differences between CD and UC patients ( p = 0.543). Among CD patients, adherence to MD was higher in patients with inactive disease ( p < 0.001) than in patients during the active phase, while no significant difference was found regarding disease activity in UC patients. A significant negative correlation of the Medi-Lite score with SIBDQ score ( r = −0.2; p = 0.040) was found. MD adherence was lower in CD patients who had undergone ≥2 surgeries, whereas for patients with UC we found no significant differences in MD adherence in relation to pervious surgery. Conclusions: Adherence to MD in IBD is influenced by disease activity, QoL and patients' surgical history. A greater adherence to MD achieved with nutritional education may help improve quality of life and modulate disease activity.